Interpretasi Hadis Man Sanna Sunnatan: Rekonstruksi Konsep Sunnah - Lubis, Muh.; Ilyas, Abustani; Yahya, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Hadith of the Prophet Muhammad SAW is the second source of law after the Qur'an. During the time of the Prophet when there was a problem that was not found in the Qur'an, the Prophet was present to answer all the problems, even when he died, the hadith became the main reference after the Qur'an. However, when there is a difference in understanding a hadith, no one is more entitled to explain its meaning so that scholars offer various methods so that there is no mistake in understanding the hadith. In this case, sunnah and bid'ah are one of the long-standing problems in determining the standards referred to in the hadith. So through this article the author examines the concept in the hadith of the prophet by using the concept of ihya' al-sunnah management as an approach to obtaining the desired meaning by limiting the study to the quality of the hadith, the explanation of the hadith and the concept of sunnah and bid'ah in the hadith of the prophet. The results of the author's research show that the quality of the hadith about sunnah and bid'ah is a sahih hadith both in sanad and matan while the explanation of the hadith shows that the sunnah in the hadith man sanna sunnatan is a good and bad deed that is traditional which is done on the basis of sin or negligence. And bid'ah in the hadith kullu bid'ah is a good or bad deed done on the basis of tasyri'